Possible advantage of imiquimod and diphenylcyclopropenone combined treatment versus diphenylcyclopropenone alone: An observational study of nonresponder patients with alopecia areata. (17th April 2016) - Wasyłyszyn, Tomasz; Borowska, Katarzyna
Abstract: The topical contact sensitiser diphenylcyclopropenone (DCP) remains one of the most effective treatment modalities for alopecia areata (AA). However, some patients (nonresponders) do not respond to this treatment because they do not have an allergic reaction to DCP. The aim of this study was to investigate the potential role of imiquimod in inducing an allergic reaction to DCP in nonresponders. In all, 20 nonresponders were recruited from a group of DCP‐treated AA patients. Of these patients, 10 were treated with DCP and topical imiquimod and 10 were treated with DCP alone. A significantly better therapeutic outcome was measured in the DCP plus imiquimod group than in the group treated with DCP alone. The potential mechanism of imiquimod may involve the role of interleukin‐12, as previously suggested in an animal model. These findings suggest that imiquimod may have the potential to improve prognosis in nonresponder AA patients treated with DCP.